Inpatient physical therapy rehabilitation provided for a patient with complete vision loss following a traumatic brain injury. (8th May 2015) - Warnecke, Jessica; Devine, Nancy; Olen, Christine
Abstract: Background : Data from the World Health Organization estimates the global incidence of traumatic brain injury resulting in hospitalization or mortality to be close to 10 million people each year. People who sustain a blast-related TBI are more likely to sustain visual impairment than people injured by other means. There is a lack of published literature regarding the most effective means to assist a patient's recovery from TBI with new vision loss. The aim of this report is to describe the physical therapy management of a person regaining functional mobility when newly blind following a blast-related TBI. Method : This case report describes the inpatient rehabilitation physical therapy (PT) services provided for a single subject who experienced a blast-related TBI with complete vision loss. Outcomes : The subject spent 3.5 weeks in IPR and participated in 21 PT sessions before being discharged home. Improvements in cognition, transfers and functional mobility with adaptations for vision loss were achieved, as well as caregiver training, to provide 24-hour supervision in the home. Discussion : Collaborating with a blind specialist teacher assisted the rehabilitation of this subject. Further research is needed regarding the effective interventions for those with TBI and vision loss.